The complete chloroplast genome of Polygonatum odoratum (Liliaceae), an endemic medicinal herb - Ze-Huan Wang; Ya-Qiong Li (Mitochondrial DNA. Part B. Resources, 2020)
In this study, we sequenced the complete chloroplast genome of Polygonatum odoratum with Illumina sequencing technology. The complete chloroplast genome length is 156,082bp, shows a typical tetrad structure, which manifests as one large and one small single copy (LSC and SSC) regions of 85,009 and 18,513bp, isolated by two inverted repeat regions (IRs) of 26,280bp. This study annotated altogether 131 unique genes, consisting of 86 protein-encoding genes, 8 rRNA and 38tRNA. According to the maximum likelihood phylogenetic tree based on 8 complete chloroplast genomes, P. odoratum shows close association with additional Maianthemum genus. The chloroplast genome-wide for P. odoratum would help to conserving the precious natural populations.